A Hierarchy of Self-Renewing Tumor-Initiating Cell Types in Glioblastoma - Chen, Ruihuan; Nishimura, Merry C.; Bumbaca, Stephanie M.; Kharbanda, Samir; Forrest, William F.; Kasman, Ian M.; Greve, Joan M.; Soriano, Robert H.; Gilmour, Laurie L.; Rivers, Celina Sanchez; Modrusan, Zora; Nacu, Serban; et al. (Cancer cell, 2010)
The neural stem cell marker CD133 is reported to identify cells within glioblastoma (GBM) that can initiate neurosphere growth and tumor formation; however, instances of CD133 − cells exhibiting similar properties have also been reported. Here, we show that some PTEN-deficient GBM tumors produce a series of CD133 + and CD133 − self-renewing tumor-initiating cell types and provide evidence that these cell types constitute a lineage hierarchy. Our results show that the capacities for self-renewal and tumor initiation in GBM need not be restricted to a uniform population of stemlike cells, but can be shared by a lineage of self-renewing cell types expressing a range of markers of forebrain lineage. ► GBM PTEN deficiency correlates with successfully expandable neurosphere culture ► Identification of self-renewing CD133 − cell type generating CD133 + and CD133 − progeny ► Evidence for lineage hierarchy of self-renewing, tumor-initiating cells in GBM ► GBM cell lineage with graded spectrum of cancer stem cell competencies